HUBUNGAN ANTARA STATUS GIZI DAN JENIS KELAMIN DENGAN KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS MARTAPURA 1 KABUPATEN BANJAR TAHUN 2020 - Sari, Eka Fidya; Yuniarti, Yuniarti; Hipni, Rubiati (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2021)
Acute Respiratory Infection (ARI) in Indonesia is still one of the main public health problems, this is due to the high infant and under five mortality rate due to ARI, namely 6\1000. Each child is estimated that 3-6 episode of experiencing ARI each year and 40%-60% of the visit to the public health center are patiens with ARI. This study aims to determine the relationship between nutritional status and gender with the incidence of ARI in toddlers in the work area of the Martapura 1 Public Health Center, Banjar Regency in 2020. This study uses secondary data from register book in the IMCI room with an analytical survey method with a cross sectional approach. The population is all toddlers in the register book in the IMCI room with a sample of 892 respondents with a total sampling method using the Spearman Rank Correation Test (Spearman Rho). The results of he study of 892 toddlers as many as 500 children under five (56,1%) had ARI, the toddlers with the most nutritional ststus were 604 under five (67,7%) with normal nutrirional status and the most gender was male as many as 516 under five (57,8%). The results of statistical tests show the value of ρ = 0,635 (ρ >α > 0,05) for nutritional status and ρ = 0,432 (ρ >α > 0,05) for gender. In conclusion, there is no relationship between between nutritional status and gender with the incidence of ARI in toddlers in the work area of the Martapura 1 Public Health Center, Banjar Regency in 2020.Keywords : ARI (Acute Respiratory Infection), Nutritional Status, Gender, Toddler.